Effects of different granulocyte colony stimulating factor regimens on patients with euploid embryo transfer in recurrent implantation failure - Karaosmanoglu, Ozge; Yuceturk, Aysen; Aslan, Ilke Ozer; Yildirim Kopuk, Sule; Utkan Korun, Zeynep Ece; Cakiroglu, Yigit; Tiras, Bulent (Frontiers in Medicine, 2025)
ObjectiveThis retrospective cohort study aimed to investigate the effects of different colony-stimulating factor regimens in patients with recurrent implantation failure who underwent euploid embryo transfer.MethodsIn total, 293 women with a history of recurrent implantation failure were included. The participants were divided into three groups: Group 1 received intrauterine granulocyte colony-stimulating factor (G-CSF) 5 days before embryo transfer; Group 2 received both intrauterine G-CSF and subcutaneous G-CSF from 5 days before embryo transfer until pregnancy; and Group 3 served as the control. Hormonal treatment included a 14-day regimen of oral estradiol followed by vaginal and intramuscular progesterone.ResultsPrimary outcomes included pregnancy, biochemical pregnancy, miscarriage, and live birth rates. The pregnancy rate (positive serum hCG) was significantly higher in group 2 compared to the control (65.9% vs. 50.5%). Group 1 had a higher pregnancy rate than the control, but the difference was not statistically significant (56.8% vs. 50.5%). Live birth rates were statistically significantly higher in Group 2 than Group 3 (55.7% vs. 40.6%). Group 2 had a higher live birth rate than group 1, but the difference was not statistically significant (55.7% vs. 47.3%). Although Group 1 had a higher live birth rate than Group 3, the difference was not statistically significant (47.3% vs. 40.6%).ConclusionAddition of subcutaneous G-CSF to intrauterine injections may be associated with improved positive pregnancy test results and live birth rates in recurrent implantation failure.